Adapting the Singapore Model to Nigeria’s Urban Management: Possibilities and Challenges - Echendu, Adaku Jane (REGION, 2022)
Nigeria and Singapore are two countries that bear some historical similarities as well as differences. Singapore has emerged as a poster child for sustainable urban development while Nigeria lags very far behind in this area. This paper analyses if, and what lessons can be drawn from Singapore to inform and improve Nigeria’s urban planning and management. Improving Nigeria’s urban planning sector is especially important considering its projected additional urban growth of 226 million by 2050. The paper employs a qualitative review of existing literature and finds that relevant lessons could be drawn from Singapore’s urban planning to positively influence sustainable urban planning in Nigeria. The contextual similarities between the countries and the current planning system in place make the chances of success high. The paper advocates a planning reform focused on adequately implementing Master Plans, strengthening its planning institutions and appropriate development control, and putting in place strong disincentives for corruption to promote sustainable urban planning and improve urban conditions and sustainability.